PENDIDIKAN ANTI KORUPSI PENANAMAN KARAKTER ANTI KORUPSI DARI USIA DINI DI SEKOLAH DASAR Al-FAIZ KOTA MEDAN - Ersa Afifa Pasya (Adabiyah Islamic Journal, 2023)
Abstract: Various ways and efforts to eradicate corruption cases in Indonesia, one of the ways and efforts to eradicate corruption in Indonesia is the establishment of the Corruption Eradication Commission (KPK) in 2002 which has uncovered corruption cases in Indonesia. Another way to fight corruption is to implement anti-corruption education from an early age, namely in elementary schools. Anti-corruption education is actually part of the Citizenship Education (PKN) subject curriculum. However, its implementation has not achieved the expected results, especially in building anti-corruption attitudes and character. Lessons only limit information guidance verbally, without giving students the opportunity to develop knowledge and logical reasoning about the immoral dimensions of corruption. This article explains that formal anti-corruption education is an important education policy that cannot be postponed any longer. This is an investment to prevent corruption in the long term. The essential nature of anti-corruption education is the synergy between the utilization of information and knowledge with the ability to make moral judgments, in order to develop students' cognition, affection and behavior as a whole and continuously. The eradication of corruption in fact cannot only be carried out by certain agencies but requires comprehensive and joint implementation by law enforcement agencies, community organizations, and individual members of society. Related to this problem, the public can also contribute to eradicating corruption, including by making complaints of criminal acts of corruption with complaint procedures and also regarding legal protection for complainants of corruption along with awards for reporters of corruption. Keywords: Anti-corruption Education, elementary school education Abstrak: Berbagai cara dan upaya untuk memberantas kasus korupsi di Indonesia, salah satu cara dan upaya dalam memberantas korupsi di Indonesia adalah pembentukan Lembaga Komisi Pemberantasan Korupsi (KPK) pada tahun 2002 yang telah mengungkap kasus korupsi di Indonesia. Cara lain untuk memerangi korupsi adalah dengan menerapkan pendidikan antikorupsi dari dini yaitu di sekolah dasar, Pendidikan antikorupsi sebenarnya merupakan bagian dari kurikulum mata pelajaran Pendidikan Kewarganegaraan (PKN). Namun implementasinya belum mencapai hasil yang diharapkan, terutama dalam membangun sikap dan karakter antikorupsi. Pelajaran hanya sebatas penyampaian informasi secara verbal, tanpa memberi kesempatan kepada siswa untuk mengembangkan pengetahuan dan penalaran logis tentang dimensi maksiat korupsi. Artikel ini menjelaskan bahwa pendidikan formal antikorupsi merupakan kebijakan pendidikan penting yang tidak dapat ditunda lagi. Ini adalah investasi untuk mencegah korupsi dalam jangka panjang. Sifat esensial dari pendidikan antikorupsi adalah sinergi antara pemanfaatan informasi dan pengetahuan dengan kemampuan membuat pertimbangan moral, guna mengembangkan kognisi, afeksi dan konasi peserta didik secara utuh dan berkesinambungan. Pemberantasan korupsi kenyataannya tidak bisa dilakukan hanya oleh instansi tertentu namun membutuhkan pelaksanaan secara komprehensif dan Bersama – sama oleh lembaga penegak hukum, lembaga masyarakat, dan individu anggota masyarakat. Terkait masalah tersebut, masyarakat juga dapat berkontribusi memberantas korupsi diantaranya dengan melakukan pengaduan tindak pidana korupsi dengan tata cara pengaduan dan juga mengenai perlindungan hukum bagi pengadu tindak pidana korupsi beserta penghargaan bagi pelapor tindak pidana korupsi. Kata Kunci: Pendidikan Anti Korupsi, Pendidikan di Sekolah Dasar